Inclusion by co-production of social housing - Murray Svidroňová, Mária (Central European Public Administration Review, 2019)
The field of social housing is one of many subjected to the potentials of co-production. Specifically, the Sustainable Development Goals target 11.1 is "By 2030, ensure access for all to adequate, safe and affordable housing and basic services and upgrade slums". The current Slovak "State Housing Policy Concept to 2020", among others, defines specific objec-tives, e.g. increasing or at least maintaining the same share of public ex-penditure on housing, introducing a new housing allowance, and support-ing the development of the non-profit sector in housing provision. The goal of this article is to investigate to what extent co-production - as joint working of the public, private for profit and private not-for profit sectors - has the capacity to address the gap in the provision of social housing in the Slovak Republic. Using the method of case study, the scale and forms of co-production in social housing are investigated and the key factors and barriers of co-production in this area are analysed. The authors sug-gest that co-production of social housing is the most efficient method of delivery of social housing, improves sustainability, and helps to include the beneficiaries into society. However, this approach requires extra en-ergy from the stakeholders - especially from public officials - and is thus still rarely used in practice.
Keywords: case study; co-production; Slovakia; social housing; social inclusion